تقويم الظروف الهيدروجيولوجية في القطاع السابع من حوض الفرات الأدنى- سورية - شريف بدر حايك; عباس عبد الرحمن (Tishreen University, 2019)
يقع القطاع السابع على الضفة اليمنى لنهر الفرات عند مدينة البوكمال على الحدود السورية - العراقية. وقد أسهم الاستثمار الزراعي الكثيف لأراضي القطاع، وعدم فعالية الصرف الطبيعي والاصطناعي، في خروج مساحات من الاستثمار الزراعي، أو انخفاض مردودها الاقتصادي. الأمر الذي تطلب تقييم موارد المياه الجوفية في منطقة البحث التي تتوضع ضمن طبقة حصويات وحصويات رملية في الأسفل، يعلوها طبقة غضار ولوم شبه نفوذة، وتشكل طبقة الغضار المارلية والجصية مستوى أساسها. تتراوح أعماق سطح المياه الجوفية بين (1-0.8) م خلال فترة (أيار2005 ـ نيسان 2007)، وتقترب من سطح الأرض خلال موسم الري. وتستجيب مناسيب المياه الجوفية الحرة لارتفاع مياه نهر الفرات ضمن مصطبة الفيضان لفترة محدودة، فينعكس الميل الهيدروليكي باتجاه اليابسة. وبسبب انتشار التوضعات التبخرية، والصعود الشعري للمياه الجوفية، وقابلية التبخر العالية وندرة الهطل المطري، انتشر التملح الثانوي لأراضي القطاع، فوصلت الملوحة العامة إلى 23 غ/لتر، وهذا أدى إلى عدم صلاحية المياه الجوفية للاستخدامات الزراعية.   Sector No. 7 located on the right side of Euphrates River near AlBukamal City on Iraq Syrian Borders. High density use of lands and low efficiency of dewatering have contributed to subtracting many lands from agricultural uses or low yield. So, we should assess  the  groundwater resources. Groundwater deposited in gravel and sandy gravel layer covered with semi-porous silt and loam layer. The base impervious layer consists of marl and gypsum. Groundwater depths range from (0.8 - 1.0 m) from May 2005 until April 2007, getting so close to ground surface during irrigation season. Groundwater responds to changes in Euphrates water surface within the floodplain which causes negative values in hydraulic slope toward the land. Expanding evaporated deposits capillary zone  groundwater arise, high evaporation capacity and inadequate rain cause secondary salinity of soils with values of 23 gr/l and the groundwater is not suitable for irrigation purposes.